COMPREHENSIVE ACCOUNT OF SARPAVISHA WITH SPECIAL REFERENCE TO BRIHATTRAYI - Tomar, Samata; Jawanjal, *Pravin Madhukar (International Journal of Ayurveda and Pharma Research, 2019)
Agadatantra (Ayurvedic toxicology) being the sixth branch of Ashtaanga Ayurveda deals with the study of Jaangam (animate) and (Sthavara) inanimate poisons, their symptoms and management. Here is an attempt to collect all references regarding Sarpa Visha described in Brihattrayi. As theory and practice are the two wings of knowledge, literature review is the foundation of applied sciences. Ancient man is forests dweller. There is a dire need of protection from plant and animal poisoning, hence branch of Agadatantra (toxicology) is well established at that time. Material and methods: Brihattrayi (Major classics) of Ayurveda had been referred for literature review. Past studies and researches regarding the topic also been probed. Objectives: To present a comprehensive account of snake management in Ayurveda. Discussion: Data is presented under the headings of snake identification, specific signs and symptoms and Vega (stage) wise treatment with Agadas and role of Agadatantra in snakebite management as a first aid. Conclusion: Systematically presented data will prove a ready reckoner for UG, PG Scholars and researchers, zoologists for easy referencing. Snake bite management through different antidotes mentioned as Agadas in classical texts. These formulations need to be researched with modern parameters of Invivo and Invitro studies.